Racial inequalities in trends in adolescent motherhood and access to prenatal care in Brazil, 2008-2019 (Research, Society and Development, 2023)
Teenage pregnancy and motherhood are issues related to human rights, sexual and reproductive rights, and public health. To identify racial inequities in nationwide temporal trends of teenage motherhood and access to antenatal visits in Brazil. A descriptive analysis of the proportion of adolescent mothers of live births, sociodemographic characteristics, and the number of prenatal visits according to race/color and age group (10-14 and 15-19 years) was performed using data from the Live Birth Information System. Trends over time were evaluated using negative binomial regression models. During the analysis period, 6.118.205 adolescents mothers were identified, with the highest proportion of mothers between 15-19 years of age (95.14%). The trend analysis showed an overall pattern of decreasing proportions of motherhood among adolescents aged 10-14 (RR=0.97; p